Thermal Stabilization of Nafion with Nanocarbon Materials - Krasnova, Anna O.; Glebova, Nadezhda V.; Kastsova, Angelina G.; Rabchinskii, Maxim K.; Nechitailov, Andrey A. (Polymers, 2023)
The stability of Nafion–carbon composites is important for the efficient functioning of fuel cells. The thermal decomposition of Nafion, nanostructured carbon materials, such as multi-walled carbon nanotubes, graphene-like materials, and their composites, have been studied using constant heating rate thermogravimetry in air. Materials were characterized by quantitative and qualitative analysis methods, such as thermogravimetry, X-ray photoelectron spectroscopy, scanning, and transmission electron microscopy with field emission. In Nafion–carbon composites, an increase in the thermal stability of the Nafion polymer is observed due to the formation of surface compounds at the Nafion–carbon interface. In this case, the degree of stabilization is affected by both the component composition of the composite and the structure of the nanocarbon material. The greatest effect was obtained in the case of using thermally expanded graphite (few-layer graphene). Nafion is distributed to a greater extent over the surface of the carbon material due to its high structural accessibility. The most thermally stable composite is Nafion–graphene in a mass ratio of components 1:4 with one stage Nafion degradation at 422 °C, whereas the degradation of pristine Nafion occurs in three stages at 341, 413, and 430 °C. The dependences of thermal stability and features of thermal degradation on the composition and structure of composites are discussed.